2015
DOI: 10.1097/cnd.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cerebrospinal Fluid Protein Levels and Electrophysiologic Abnormalities in Guillain–Barré Syndrome

Abstract: This retrospective study is the first to demonstrate a relationship between the CSF protein level and the electrophysiologic abnormalities that accompany GBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Higher CSF protein levels have been reported to show a significant loss of the blood brain barrier integrity 21 . Prognostic implications of CSF protein levels for disease activity have been shown in previous studies 6,15,22 . Our study was compatible with previous studies, and we found that higher CSF protein levels were correlated with worse prognosis on both the first day and first month.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Higher CSF protein levels have been reported to show a significant loss of the blood brain barrier integrity 21 . Prognostic implications of CSF protein levels for disease activity have been shown in previous studies 6,15,22 . Our study was compatible with previous studies, and we found that higher CSF protein levels were correlated with worse prognosis on both the first day and first month.…”
Section: Discussionmentioning
confidence: 63%
“…Early predictions enable clinicians to provide proper and cost-effective treatments. Many studies have investigated the prognostic determinants of GBS 6,8,12,13,14 . We evaluated the clinical course at the end of the first day and first month, and we found that patients who satisfied a higher number of demyelinating criteria and exhibited higher CSF protein levels had increased disability scores in the first day and first month.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations